Analisa Keamanan Tanda Tangan Digital Dengan Menerapkan Metode AHA-1 - Janisah Janisah; Lince Tomoria Sianturi; Candra Frenki Sianturi; Murdani Murdani (STMIK Budi Darma, 2021)
The importance of information value causes often the information desired by certain people can then modify it. To be able to validate the information obtained, authentication must be done so that the authenticity of the information is known. Signature is a marker or identity in a document. Signatures have an important role in verifying and legalizing documents. To secure digital signatures, a hash function can be processed, a hash consisting of a Secure Hash Algorithm. The Secure Hash Algorithm (SHA-1) method is a hash function that works in one direction, this means that messages that have been converted into message digest cannot be returned to the original message. Two different messages will always produce different hash values, and results from different string length input will result in an autput with a fixed string length of 160 bits.